Ampliación de la distribución de Gerrhonotus infernalis (Squamata: anguidae) para la región noreste del estado de Guanajuato - Villegas-Ruiz, Joaquín; Hernández Árciga, Raúl; Elizalde-Arellano, Cynthia (Instituto de Ecología, A.C., 2015)
Establishing the limits on the distribution of Gerrhonotus infernalis in Guanajuato state has been relatively complicated, and the presence of this species was uncertain until recently. This paper confirms the presence of Gerrhonotus infernalis for the state, expanding the range of the distribution known for the northeast of the state based on three records from the Sierra Gorda.